2007
DOI: 10.1002/art.22300
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and chondroinduction of a dermis‐isolated, aggrecan‐sensitive subpopulation with high chondrogenic potential

Abstract: Objective. To develop a process that yields tissueengineered articular cartilage constructs from skinderived cells.Methods. Dermis-isolated, aggrecan-sensitive (DIAS) cells were isolated using a modified rapid adherence process. The chondrogenic potential was measured by quantitative reverse transcriptase-polymerase chain reaction, enzyme-linked immunosorbent assay, and immunohistochemistry. Filamentous actin (Factin) and vinculin organization was detected using fluorescence microscopy.Results. The rapid adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…Our group has found that adult dermal fibroblasts are capable of chondrogenic differentiation when cultured on the aggrecan, the main proteoglycan found in cartilage [13]. We showed that a subpopulation with high chondrogenic potential, termed dermis-isolated adult stem (DIAS) cells, could be selected through rapid adherence to tissue culture polystyrene surfaces [18], [19]. We also demonstrated the ability of DIAS cells to not only produce cartilage-like extracellular matrix (ECM), but also form tissue engineered constructs with robust mechanical properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has found that adult dermal fibroblasts are capable of chondrogenic differentiation when cultured on the aggrecan, the main proteoglycan found in cartilage [13]. We showed that a subpopulation with high chondrogenic potential, termed dermis-isolated adult stem (DIAS) cells, could be selected through rapid adherence to tissue culture polystyrene surfaces [18], [19]. We also demonstrated the ability of DIAS cells to not only produce cartilage-like extracellular matrix (ECM), but also form tissue engineered constructs with robust mechanical properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…Adult stem/progenitor cells are also known to exist in the dermis [13][14][15][16][17][18][19][20]. These cells can be characterized into various cell types, including those that differentiate into adipocytes, chondrocytes, smooth muscle cells, and osteoblasts, and those that differentiate into nonmesodermal cells, including neural cells, hepatocytes, and pancreatic cells [13][14][15][16][17][18][19][20]43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Adult stem cells exist in multiple tissues of the body, including the bone marrow [2][3][4][5], brain, skeletal muscle [6], adipose tissue [7,8], umbilical cord [9], and placenta [10]. The skin is the largest organ in the body, and its stem cells have been identified in all regions of the skin, including the epidermis [11,12], dermis [13][14][15][16][17][18][19][20], and hair follicles [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent study, a protocol was developed to isolate a subpopulation that displayed greater chondroinduction potential, termed DIAS cell, from whole dermis by rapid adherence. It was demonstrated that DIAS cells can be used to form cartilage neocartilage, suggesting that skin-derived stem cells can be differentiated to chondrocyte-like cells [98].…”
Section: The Potential Of Dias Cells To Formmentioning
confidence: 99%